Implementasi Model Problem-Based Learning terhadap Peningkatan Critical Thinking dalam Pendidikan Jasmani - Fatin, Nuri Nuraini; Subroto, Toto; Rahmat, Alit (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was conducted to learn about implementing the problem-based learning model to improve critical thinking in physical education. This research study aims to analyze the impact of using problem-based learning on increasing critical thinking in physical education and its influence on the 21st century. The research method used is the Systematic Literature Review research method using a qualitative approach. The data collection used was by collecting other literature studies resulting from research in 18 examinations taken from 7 sources, which were included in a systematic review based on the quality of the sources. The results show that problem-based learning can be a practical approach for improving students' critical thinking skills. In conclusion, problem-based learning can enhance students' learning experiences, encourage critical thinking, and increase deeper understanding of concepts and facts. Keywords: Problem-Based Learning, Critical Thinking, 21st Century